In vivo Therapeutic Effects and Mechanisms of Hydroxyasiaticoside Combined With Praziquantel in the Treatment of Schistosomiasis Induced Hepatic Fibrosis - Fang, Huilong; Yu, Ling; You, Da; Peng, Nan; Guo, Wanbei; Wang, Junjie; Zhang, Xing (Frontiers in Bioengineering and Biotechnology, 2021)
Schistosomiasis has been a fatal obstinate disease that threatens global human health, resulting in the granulomatous inflammation and liver fibrosis. Objective:The aim of this study was to evaluate the therapeutic effects and mechanisms of hydroxyasiaticoside combined with praziquantel in the treatment of schistosomiasis-induced liver fibrosis. Methods:Mice were randomly distributed into four experimental groups: normal control group, model group, praziquantel group, praziquantel + hydroxyasiaticoside group. Except for the normal control group, they were infected with Schistosomia cercariae through the abdominal skin to induce liver fibrosis. In the intervention group, mice were administered with the respective drugs by gavage after 8 weeks of infection. At the end of the treatment, mice were sacrificed to collect blood for the determination of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) serum levels. Moreover, the liver was excised, weighed, and liver indices were calculated. Histopathological examination was performed to assess liver morphology. Besides, the expression of collagen type I and III in liver was determined; the mRNA expression levels of IL-6 and TNF-α in liver tissues were measured using Real-time PCR while ELISA and western blotting were performed on liver tissue homogenate to determine the protein expression of IL-6 and TNF-α. Results:The combination of praziquantel and hydroxyasiaticoside lowered the pathological scores of schistosomiasis-induced hepatic fibrosis, the liver indice, serum AST and ALT levels, improved liver morphology, downregulated the expression levels of hepatic type I and III collagen, inhibited the mRNA expression levels of pro-inflammatory factors (IL-6 and TNF-α) in the liver of mice relative to the praziquantel alone. Conclusion:The combination of hydroxyasiaticoside and praziquantel is a potential therapeutic option for schistosomiasis-induced hepatic fibrosis. Notably, this combination noticeably suppresses the protein and mRNA expression levels of pro-inflammatory factors (TNF-α and IL-6) in the liver.